An investigation of the relationship between HbA1c and blood zinc levels in diabetes patients, who attending to Boumansour Diabetes and Heart Center in the city of Derna, Libya - Saad S. khagkhag; Mahmoud A. Alhosni; Ashraf S. Elzer; Abd Almoain S. Nasib (المجلة الأفروآسيوية للبحث العلمي, 2024)
Background: Diabetes is a chronic illness that develops when the body is unable to use insulin efficiently or when the pancreas is unable to produce insulin at all. Zinc (Zn) is a vital metal with several roles in cellular metabolism. They include insulin regulation and carbohydrate metabolism. Aims and Objective: The current study was aimed at analyzing serum zinc levels among diabetic patients and determining the correlation between serum zinc levels and HbA1c among diabetic patients. Materials and Methods: The study involved a total of one hundred patients. Estimation of blood glucose (Fasting). Glycated haemoglobin (HbA1c) and serum Zinc was done. Statistical Analysis: The data is collected and analyzed statistically to determine the significance of different parameters by using the SPSS package for Windows version 25.0. Results: Serum zinc and HbA1c levels have a slight negative correlation (R=0.263, P value = - 0.008). Conclusion: Conclusion: This study concluded that there is a mild negative correlation between serum Zn with HbA1c. It is important to estimate the level of ZN in diabetic patients to know their insulin status and prevent complications. It has been demonstrated that supplementing with zinc can improve lipids, haemoglobin A1c (HbA1c), and plasma glucose in prediabetics and diabetics. It may also enhance insulin sensitivity, lessen oxidative stress, and guard against kidney damage.